Evaluating teacher performance in implementing differentiated learning using the discrepancy model - Irene Septinna Nugrahani; Yari Dwikurnaningsih; Wahyudi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to evaluate teacher performance through the implementation of differentiated learning at SDN Randuacir. The program evaluation was conducted by identifying discrepancies between the government's standards for differentiated learning and the actual implementation at the school. This research employs an evaluative qualitative approach using the Discrepancy Evaluation Model developed by Malcolm Provus, which consists of five stages: design, installation, process, product, and cost-benefit analysis. The subjects of this study were the principal and teachers. Data were collected through interviews, observations, and documentation. The data analysis involved data reduction, data presentation, and conclusion drawing. The findings reveal that discrepancies were present in all stages, including design, installation, process, product, and cost-benefit analysis. These discrepancies were primarily due to the inadequate execution of the design stage. It is concluded that teacher performance has not yet reached its optimal level and needs improvement, particularly in pedagogical, professional, and social competencies.